Mediating factors in retirement savings and well-being: a focused study on Sarawak - Suzie, Adee; Evan, Lau; Shirly, Wong (Informa UK Limited, trading as Taylor & Francis Group, 2024)
This study aims to examine the factors that influence societal savings habits and preretirement well-being. Triggered by the global trend of low personal interest rates, it seeks to illuminate how preparedness for retirement affects the overall quality of life and societal well-being. More specifically, the study pursues three (3) main objectives: 1) to identify the socio-demographic and behavioural elements that shape societal savings habits; 2) to determine the factors that affect individuals’ propensity to save; and 3) to assess the impact of savings behaviours on pre-retirement well-being, focusing on aspects such as happiness, prosperity, health, comfort, and security. We used the Partial Least Squares Structural Equation Model (PLS-SEM) with SMART-PLS to analyse these relationships. The results illustrate significant correlations among financial literacy, savings habits, financial risk tolerance, future time perspectives, retirement savings, and retirement well-being. These findings bolster the study’s conclusions, which are further supported by active survey participation